Transforming Belmont Estate: a strategic plan - Nyack-Compton, Shadel (Kansas State University, 2011)
Transforming Belmont Estate from a traditional agricultural production business into a profitable agri-tourism enterprise is the issue addressed in this thesis. The importance of this problem rests on the fact that the author is the general manager of this family business and needs to organize it in ways that facilitates its ability to keep growing in a rapidly changing market environment. Given the increasing positioning of Grenada as a preferred tourist destination and the increasing number of people who are responding to this positioning, the management of Belmont Estate believes that transforming this traditional agricultural production business into an agritourism business will create significant value for shareholders and stakeholders. The process of transforming the organization needs to start with a new way of envisioning it. Therefore, a strategic direction and a compelling value proposition were developed. An assessment of the business environment was conducted to develop a framework where specific strategies could be developed to support the new strategic direction that has been established. Additionally, a financial analysis that focused on the contribution of the different enterprises to the new strategic direction was conducted to assess the potential financial outcome of this effort. The results show that Belmont Estate is well-positioned to benefit from increasing tourism business in Grenada. If the management of Belmont Estate can implement the strategic plan, it can successfully transform Belmont Estate from an agricultural production business into an efficient agritourism business that not only creates value for its shareholders and stakeholders but offers a welcome diversity to Grenada’s growing tourism industry.
Keywords: Agritourism; Grenada; Tourism; Visioning; Business Administration, Management (0454); Economics, Agricultural (0503)